The STELLA Robotic Observatory on Tenerife - Klaus G. Strassmeier; Thomas Granzer; Michael Weber; Manfred Woche; Emil Popow; Arto Järvinen; Janos Bartus; Svend-Marian Bauer; Frank Dionies; Thomas Fechner; Wilbert Bittner; Jens Paschke (Advances in Astronomy)
The Astrophysical Institute Potsdam (AIP) and the Instituto de Astrofísica de Canarias (IAC) inaugurated the robotic telescopes STELLA-I and STELLA-II (STELLar Activity) on Tenerife on May 18, 2006. The observatory is located on the Izaña ridge at an elevation of 2400 m near the German Vacuum Tower Telescope. STELLA consists of two 1.2 m alt-az telescopes. One telescope fiber feeds a bench-mounted high-resolution echelle spectrograph while the other telescope feeds a wide-field imaging photometer. Both scopes work autonomously by means of artificial intelligence. Not only that the telescopes are automated, but the entire observatory operates like a robot, and does not require any human presence on site.